P5 Epicardial adipose tissue volume and characteristics are associated with stage B heart failure in type 2 diabetes. (21st September 2022) - Ayton, Sarah L; Yeo, Jian L; Gulsin, Gaurav S; Dattani, Abhishek; Brady, Emer M; Ranjit Arnold, J; Graham-Brown, Matthew PM; Singh, Anvesha; Dey, Damini; McCann, Gerry P; Moss, Alastair J
Abstract : Objective: To assess whether epicardial adipose tissue (EAT) is associated with early cardiac dysfunction in type 2 diabetes (T2D). Methods: Prospective case-control study. Participants with T2D and no known cardiovascular disease underwent comprehensive multimodality phenotyping. CT derived EAT volume was measured using a deep learning method and indexed to body surface area. Total EAT was quantified using CT adipose tissue attenuation range of -30 to -190 Hounsfield Units (HU) and low attenuation EAT as -90 to -190 HU. Left ventricular (LV) volumes, strain and diastolic function were assessed using cardiac MRI and echocardiography. Results: Two hundred and fifteen T2Ds (median age 63 years, 60% male) and 39 controls (median age 59 years, 62% male) were included. T2Ds had higher LV mass/volume ratio (median 0.89 (0.82, 0.99) vs 0.79 (0.75, 0.89)), reduced global longitudinal strain (GLS; mean 16.13±2.33% vs 17.18±2.16%) and worse diastolic function (lower circumferential peak early diastolic strain rate and average E/e'). Total and low attenuation indexed EAT volumes were 1.6-fold and 2-fold higher, respectively, in subjects with T2D. After adjustment for age, sex, ethnicity, systolic blood pressure and waist/hip ratio, low attenuation indexed EAT volume was independently associated with LV mass/volume ratio (ß= 0.002, p= 0.03) and GLS (ß= -0.03, p= 0.03) and total indexed EAT volume with GLS (ß= -0.02, p 0.02), but neither were independently associated with indices of diastolic dysfunction in T2D. Conclusion: EAT volumes are higher in T2D, and excess EAT accumulation is independently associated with early markers of cardiac dysfunction.